Mass inoculation and rural rhythms : local agents, population data, and restructured social systems during the cholera pandemic in China, 1962–1965 - Fang, Xiaoping (2021)
This article examines the dynamics between the mass inoculation campaigns and China’s restructured rural social system during the 1962–1965 cholera pandemic, with a focus on the role of local agents and population data during the integration of the medical and administrative systems. The inoculation campaigns not only harnessed local agents and household and accounting information provided by the broader social restructuring initiatives but also directly contributed to these by compiling inoculation registers and certificates. These campaigns included the administrative and medical systems and combined social, production, and epidemiological data in a reciprocal process. The mass inoculations therefore functionalized social control; facilitated the formation and top-down imposition of a new, broad-reaching social structure; and contributed to the formation of a sedentary society. In this sense, these inoculation campaigns were a significant social and political exercise rather than just a pathological, medical, and health incident.